Medical, healthcare, and emergency model : Mobile web to enhance patients’ facilities - Hameed, Shihab A.; Miho, Vladimir (2010)
Over the past few years, telemedicine has made considerable progress. Its benefits range from the ability to monitor patient’s progress remotely to providing high quality of care to a larger geographic segment of patients. Many of the current Malaysian medical information, healthcare, and emergency systems suffers from locality, stand alone, and lack of fully utilize the great facilities of Internet, multimedia, wireless and real time technologies. To overcomes many of the current problems; this research project focuses on developing a novel model for an integrated Medical, Healthcare, and Emergency using Internet, wireless, multimedia, and real time technologies. This paper focuses on developing a mobile web to enhance patients’ facilities. It is based on W3C web standards which, allows patients to access their account from any mobile phone with capabilities of connecting to the Internet. Features such as searching for healthcare centers and doctors, providing address and driving directions to the nearest hospital or health care center, requesting an ambulance and viewing personal details are provided. The proposed model offers centralized medical patient records that can be viewed and updated by physicians using any web browser. A prototype for the proposed model is implemented using open source technologies and samples of results are provided.